Plasma mcfDNA Sequencing May Improve Usual Care Diagnostics to Detect HHV-8 Among Outpatient People with Advanced HIV - Sarah Park; Brian Epling; Morgan Richey; Daniel Lupu; Mona Mughar; Irini Sereti (Pathogens and Immunity)
Background: Human herpesvirus-8 (HHV-8), or Kaposi sarcoma (KS)-associated herpesvirus (KSHV), causes severe disease in people with profound immunosuppression. Yet, diagnosing KS can be challenging given the diverse manifestations and current limited usual care diagnostic methods (UC; polymerase chain reaction, histopathology).